The histopathological features of the nail plate in pachyonychia congenita. (9th January 2020) - Stewart, Campbell L.; Takeshita, Junko; Hansen, C. David; Rubin, Adam I.
Abstract: Background: Pachyonychia congenita (PC) is a rare autosomal dominant disorder of keratinization mediated by genetic mutations in KRT6A, KRT6B, KRT6C, KRT16, or KRT17 . While nail dystrophy in PC has a significant impact on quality of life, the histopathological features of the nail plate in PC have not been previously reported. We report the histopathological features of nail plates provided by 19 patients with genetically confirmed PC. Methods: Nineteen patients with genetically confirmed PC provided a total of 56 nail plates for histopathologic examination. The nail plates were examined for the presence of hyphae, yeast, bacteria, neutrophils, parakeratosis, plasma globules, and hemorrhage. Specimens with onychomycosis (three patients) were excluded from the analysis. Results: No specific histopathological feature was identified in PC nails. Parakeratosis and plasma globules were the most prominent features in both clinically affected and unaffected PC nails. There was a significant association between clinical dystrophy of all 20 nails and KRT6A mutations, and a lack of dystrophy of all 20 nails in KRT6B mutations. Conclusions: Parakeratosis and plasma globules in the absence of other inflammatory disorders should raise PC in the histopathologic differential diagnosis. The presence of onychomycosis in a nail plate does not exclude a diagnosis of PC.